Pengaruh Kualitas Kehidupan Kerja dan Budaya Organisasi Terhadap Kepuasan Kinerja Karyawan pada Staf Homesick Vapestore Kota Bandung - Wala Erpurini; Moch Badrudin (Yayasan Literasi Sains Indonesia, 2023)
This research was conducted on Homesick Vapestore Employees in Bandung. The purpose of this study was to find out how much the influence of Quality of Work Life and Organizational Culture contributes to satisfaction of performance both partially and simultaneously at Homesick Vapestore Bandung. The research method that will be used in this research is descriptive and associative method. In this study, the unit of analysis was individuals, namely employees of the Bandung Homesick Vapestore. The sample in this study were 36 respondents. Saturated sampling is the sampling technique used in this study. The analytical method uses multiple linear regression analysis, in addition to testing the validity and reliability of the research instrument. Based on the results of the study indicate that there is influence both partially and simultaneously on the independent variables Quality of Work Life and Organizational Culture on Performance Satisfaction. The implication of this research is that homesick Vapestore Bandung can make various improvements between fellow employees and superiors by establishing good communication such as complete and clear information on goods / services, there is cooperation such as careful decision making of problems to create good solutions and innovations with openness among employees and superiors that results in satisfaction with their performance.